Resonant x-ray diffraction as a tool to calculate mixed valence ratios: Application to Prussian Blue materials - Ferreira, Fabio Furlan; Bueno, Paulo Roberto [UNESP]; Setti, Grazielle O. [UNESP]; Gimenez-Romero, David; Garcia-Jareno, Jose Juan; Vicente, Francisco (American Institute of Physics (AIP), 2008)
An approach is proposed here to calculate mixed valence ratios in molecular compounds. Synchrotron x-ray powder diffraction experiments were conducted to determine the Fe(+3)/Fe(+2) ratio in Prussian Blue compounds, which were elected as an example of the use of this approach. As a result, a resonant x-ray diffraction measurement provided direct evidence that the vacant [Fe(CN)(6)] group was randomly absent from similar to 31% of the structure, which was indicated by structural differences caused by variations in the anomalous dispersion term. These findings are very important for a deeper understanding of the changes occurring in properties during in situ compositional variations. (c) 2008 American Institute of Physics.